PENGEMBANGAN MEDIA PEMBELAJARAN SEJARAH POWTOON BERBASIS INQUIRY LEARNING UNTUK MENINGKATKAN CRITICAL THINKING SKILLS DENGAN MENGGUNAKAN MODEL ASSURE - Puji Rizki Irani; Sumardi Sumardi; Nurul Umamah (Candrasangkala: Jurnal Pendidikan dan Sejarah, 2022)
Abstract: The paradigm of independent learning and the development of digital technology have brought major changes in the historical learning. Educators are required to innovate in learning in order to develop students' critical thinking skills (CTS). However, the results of previous studies and preliminary observations showed problems related to the low CTS of students. The purpose of this research and development is to provide an alternative solution to the low CTS of students by developing a media powtoon based on inquiry learning. The design uses the ASSURE development model stages. The result of research and development is powtoon media based on inquiry learning, which is validated by experts and can improve CTS. The results of the validation of content experts in the field of study reached 94% with "very good" qualifications, media or design validation reached 91.8% with "very good" qualifications, and language validation reached 94% with "very good" qualifications. Furthermore, the results of the user trial reached 94% with a "very good" qualification. The results of small group trials and field trials obtained an increase in CTS of 80.83% and 81.65% with the predicate "very high". So it was concluded that the media powtoon based on inquiry learning was effective in improving students' CTS.Abstrak: Paradigma merdeka belajar dan perkembangan teknologi digital membawa perubahan besar dalam pembelajaran sejarah. Pendidik diharapkan berinovasi dalam pembelajaran guna mengembangkan Critical Thinking Skills (CTS) peserta didik. Namun hasil penelitian terdahulu dan observasi awal, menunjukkan permasalahan terkait rendahnya CTS peserta didik. Tujuan penelitian dan pengembangan ini adalah memberikan solusi alternatif rendahnya CTS peserta didik dengan mengembangkan media Powtoon berbasis Inquiry Learning. Desain menggunakan tahapan pengembangan model ASSURE. Hasil penelitian dan pengembangan adalah media Powtoon berbasis Inquiry Learning yang tervalidasi ahli dan dapat meningkatkan CTS. Hasil validasi ahli isi bidang studi mencapai 94% dengan kualifikasi “sangat baik”, validasi media atau desain mencapai 91,8% dengan kualifikasi “sangat baik”, dan validasi bahasa mencapai 94% dengan kualifikasi “sangat baik”. Selanjutnya hasil uji coba pengguna mencapai 94% dengan kualifikasi “sangat baik”. Hasil uji coba kelompok kecil dan uji coba lapangan memperoleh peningkatan CTS sebesar 80,83% dan 81,65% dengan predikat “sangat tinggi”. Sehingga disimpulkan bahwa media Powtoon berbasis Inquiry Learning efektif meningkatkan CTS peserta didik.